2014
DOI: 10.1080/09593330.2014.902112
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coligrowth and transport in the presence of nanosilver under variable growth conditions

Abstract: Nanosilver (silver nanoparticles) has the ability to anchor to the bacterial cell membrane and subsequently penetrate it, thereby causing structural changes (i.e., permeability) in the cell membrane and death of the cell. The bacterial responses to the presence of nanosilver usually vary depending on the concentration of nanosilver particles, exposure time and the bacterial physiological stage. Since bacterial anabolism dependents upon a stoichiometric ratio of carbon and inorganic elements (nutrients), the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Some authors have reported that the presence of biosurfactants can increase the resistance to some pathogenic microorganisms. For instance, Xie et al [58] have reported that the presence of rhamnolipid increased the resistance of E. coli to Ag NPs. Therefore, this fact can be related to the higher biocompatible character of these NPs in comparison with the NPs obtained in the absence of biosurfactants.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have reported that the presence of biosurfactants can increase the resistance to some pathogenic microorganisms. For instance, Xie et al [58] have reported that the presence of rhamnolipid increased the resistance of E. coli to Ag NPs. Therefore, this fact can be related to the higher biocompatible character of these NPs in comparison with the NPs obtained in the absence of biosurfactants.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it is known that the substrate roughness affects the adhesion of the bacteria. [86][87][88] With a careful electropolishing process, the stainless steel would have a microscopically smoother surface, leading to a decreasing bacterial attachment. 89 The selection of the electropolishing electrolyte of the stainless steel has some prerequisites: a.…”
Section: Basic Control Parameters Governing the Performancementioning
confidence: 99%
“…Production of nano-biosurfactants was achieved and it will help to replace synthetic nano-emulsions (Saeedi et al, 2014). A recent discovery showed that the presence of a rhamnolipid biosurfactant increased the resistance of E. coli to nanosilver (Xie et al, 2014). This study may facilitate a new line of research on enhanced nanosilver synthesis by engineered E. coli cells.…”
Section: Biosurfactant-assisted Greener Synthesis Of Nanoparticlesmentioning
confidence: 95%